Two-Phase Multi-Point Design Exploration of Submerged Nacelles for Marine Propulsive Pump Installation - Filippo Avanzi; Andrea Magrini; Francesco De Vanna (Journal of Marine Science and Engineering)
Outboard Dynamic-inlet Waterjets (ODW) are axisymmetric units, powered by a self-contained pump, that, by processing a uniform undisturbed streamtube, can operate more efficiently than conventional marine propulsors. This feature also provides methodological convenience, enabling accurate numerical investigations of the system alone using 2D axisymmetric models. Leveraging this property, the present study bridges the gap on the design principles required to tailor ODW geometries across multiple operating conditions. Reynolds-Averaged Navier Stokes (RANS) equations are solved, including turbulence and cavitation models, to draw the propulsor’s characteristic maps and identify two relevant operating points, set by the combination of a specified pump rotational regime with an advancing velocity. Simulations for these in- and off-design conditions are systematically performed over a database of 512 randomly sampled geometric variants. The corresponding results show that optimised shapes improving the inlet Pressure Recovery (PR) and nacelle drag at cruise conditions result in beneficial outcomes also at take-off operations, where lip cavitation may occur. Thus, analysing together the off-design PR and the cruise net force underscores their conflicting behaviour. In fact, while nacelles shortened by <semantics>12%</semantics> can reduce overall drag and enhance nominal net thrust by <semantics>2%</semantics>, designs featuring a <semantics>34%</semantics> wider capture area improve off-design PR by over <semantics>1.5%</semantics>, albeit at the cost of compromised propulsive efficiency under any operating range.